Optimized clinical practice for superaged patients with hip fracture: significance of damage control and enhanced recovery program - Zaiyang Liu; Jun Zhang; Kaiqi He; Yumei Zhang; Yuan Zhang (Burns & Trauma, 2019)
Abstract With the advent of global aging, the incidence, mortality, and medical costs of hip fracture among aged patients are increasing annually. The number of controlled clinical studies and health economics analyses that conform to evidence-based medicine principles is growing day by day. However, unfortunately, no specific recommendations regarding the procedures for the treatment of hip fracture are available. Meanwhile, the existence of both traditional treatment systems and new treatment theories means that most doctors confront difficult choices in their daily practice. These factors make the therapeutic approach for aged patients, especially among superaged patients with hip fracture, extremely challenging. This study focuses on superaged patients (> 80 years as defined by the World Health Organization) with hip fracture and includes their preoperative pathological condition; therapeutic decision-making in terms of the benefit and risk ratio, damage control theory, and enhanced recovery after surgery were also investigated. These patients were discussed specifically by combining the current treatment strategies from several experts and the results of a meta-analysis published recently. The study presents some new ideas and approaches currently recognized in the field, such as preoperative assessment, surgical planning, safety consideration, complication intervention, and enhanced recovery implementation, and further presents some clear interpretations regarding misunderstandings in clinical practice. Finally, optimized treatment according to damage control principles and enhanced recovery after surgery during the perioperative period among superaged hip fracture patients is defined.